DETERMINAN PENERAPAN ETIKA BISNIS ISLAM (STUDI PADA PELAKU USAHA DI KOTA KENDARI) (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2016)
This study aimed to examine the determinants of Islamic business ethics implementation in Kendari city. It used primary data that were obtained through interviews and open questionnaires to business owners in Kendari who claimed that they implement sharia principles on business. The samples were 24 respondents that were obtained by snowball sampling. Data were analyzed descriptively in percentage. The results showed that: The majority of respondents (66.67 %) are motivated by reward from Allah in applying Islamic business ethics; and 20.83 % are motivated by business success. While the others are motivated by dakwah and business progress. The main determinants to apply Islamic business ethics are the understanding of religious values; family factor, and social environment. No one respondent who answered that the state system is as the determinant of the Islamic business ethics implementation.